On the numerical simulation of turbulent pipe flow pattern using comsol multiphysics (2013)
In this paper, two dimensional pipe of length 0.8m and diameter 0.3m, 0.4m, and 0.45m were simulated respectively using Comsol Multiphysics 4.0 software. The governing equations and the k.ε model which accounts for the turbulent kinetic energy k and turbulent dissipation rate ε were solved using the simulator. The behaviors of the fluid were investigated at radius of 0.23m, 0.33m, and 0.38m respectively near the pipe wall to study its possible impact on the pipe wall. Changing in flow pattern with increasing velocity was observed which may cause a phenomenon such as heat transfer and consequently increase the mixing rate of dissolved substance. However, the results showed there is an indication that the inner wall of the pipes coated with thin film that reduces corrosion gradually decreases down the pipes due to the impact of the turbulent kinetic energy and turbulent dissipation rate on the pipe walls.